2014
DOI: 10.1074/jbc.m114.593491
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Tis11 Protein and Its Effects on mRNA Expression in Flies

Abstract: Background: Insects generally express a single tristetraprolin family member, zinc finger proteins that promote mRNA decay. Results: The Drosophila protein, Tis11, can promote mRNA decay in cells, and its deficiency in flies results in accumulation of certain mRNAs. Conclusion: Tis11 deficiency in Drosophila results in increases of potential target transcripts. Significance: Tis11 can affect post-transcriptional gene expression in adult flies by regulating mRNA decay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 59 publications
(88 reference statements)
1
29
0
Order By: Relevance
“…A synthetic peptide comprising the TZF domain of human TTP bound to this 9-mer sequence with a K d of 3.2 nM at 24°C, as shown by fluorescence anisotropy (11). Remarkably similar affinities have been demonstrated for the analogous TZF domains from TTP family members from a variety of other species, including the single family members expressed in Drosophila melanogaster (5), the fission yeast Schizosaccharomyces pombe (4,7), and the human pathogenic yeast Candida albicans (6). In the experimental situations tested to date, mutation of any one of the cysteines or histidines that comprise the two zinc coordination centers of the TZF domain will abrogate RNA binding.…”
Section: Tristetraprolin (Ttp)mentioning
confidence: 79%
“…A synthetic peptide comprising the TZF domain of human TTP bound to this 9-mer sequence with a K d of 3.2 nM at 24°C, as shown by fluorescence anisotropy (11). Remarkably similar affinities have been demonstrated for the analogous TZF domains from TTP family members from a variety of other species, including the single family members expressed in Drosophila melanogaster (5), the fission yeast Schizosaccharomyces pombe (4,7), and the human pathogenic yeast Candida albicans (6). In the experimental situations tested to date, mutation of any one of the cysteines or histidines that comprise the two zinc coordination centers of the TZF domain will abrogate RNA binding.…”
Section: Tristetraprolin (Ttp)mentioning
confidence: 79%
“…The exception, CR33963 (Fig. 6A,E), lies within the first intron of the gene Tis11, which encodes an RNA-binding protein that regulates mRNA stability (Choi et al 2014). Although the Hox complex lncRNA transcripts are generally expected to have nuclear roles in transcriptional regulation, a significant proportion of these RNAs was found in the cytoplasm.…”
Section: Expression and Subcellular Localization Of Lncrnasmentioning
confidence: 99%
“…Studies in cultured Drosophila S2 cells in which Tis11 was knocked down revealed a large number of stabilized transcripts, many of which contained potential binding sites [59]. Transfection of cultured mammalian cells with cDNAs expressing normal and mutant Drosophila Tis11 showed that the fly protein could bind to the optimal mammalian binding site on RNA, and could promote mRNA deadenylation and decay in a manner almost identical to human TTP [60]. As shown before in transfection experiments with human TTP, the activity of the fly protein was partially dependent on the presence of the conserved C-terminal NOT1 binding domain.…”
Section: Loss Of Function Mutationsmentioning
confidence: 99%
“…As shown before in transfection experiments with human TTP, the activity of the fly protein was partially dependent on the presence of the conserved C-terminal NOT1 binding domain. Knock-down and KO studies in adult flies demonstrated the accumulation of many potential targets, but there was almost no overlap between the transcripts accumulating in the fly and in the S2 cells [60]. It will be interesting to determine whether the putative targets identified in S2 cells will correspond more closely to flies at a different developmental stage.…”
Section: Loss Of Function Mutationsmentioning
confidence: 99%